Understanding the severity of depression: do nondepressive symptoms influence global ratings of depression severity?. (12th August 2020) - Zimmerman, Mark; Balling, Caroline; Chelminski, Iwona; Dalrymple, Kristy
Abstract: Objective: Almost all depression measures have been developed without discussing how to best conceptualize and assess the severity of depression. It is therefore not surprising that measures differ in both how items are rated and item content. The question that we address in the present report from the Rhode Island Methods to Improve Diagnostic Assessment and Services (MIDAS) project is whether a measure of depression severity should include symptoms that are frequent in depressed patients but are defining features of other disorders (eg, anxiety, irritability) Methods: Patients were evaluated with a semi-structured interview and severity ratings were made of each symptom of major depressive disorder (MDD) as well as anxiety, irritability, and somatization. Patients were also rated on the Clinical Global Index of severity (CGI). Results: Three of the 5 nondepressive symptoms (psychic anxiety, somatic anxiety, and subjective anger) were significantly correlated with the CGI. The correlation between the sum of all 5 nondepressive symptoms and the CGI was significantly lower than the correlation between the sum of the depressive symptom severity ratings (0.12 vs 0.52, z = 11.0, p < .001). The partial correlation between the CGI and the nondepressive symptom severity ratings (after controlling for the total depressive symptom ratings) was nonsignificant. Discussion: After accounting for the severity of depressive symptoms, the severity of the nondepressive symptoms was not associated with global ratings of depressive severity. These findings raise questions regarding the appropriateness of including ratings of anxiety, irritability, and somatization on a measure that purportedly assesses the severity of depression.